The Effect of Distributed and Massed Exercise Scheduling Using the DWDM Device on Improving the Accuracy of Direct Free Kick Scoring in Football for Students - Assistant Professor Dr. Waleed Sameer Hadi (Global Scientific Publishing, 2025)
The direct free kick is a skill of significant importance in football. However, the challenge lies in The absence of a similar training tool. Research Problem: Does gaining knowledge of thru disbursed and massed workout techniques the usage of the DWDM tool make contributions to teaching the direct loose kick skill?
Keywords: Multi-Task Defensive Wall Device; Distributed and Massed Exercise Scheduling; Direct Free Kick